Services Marketing - Stop, Observe, Go - Agrawal, A. K. (Indian Journal of Marketing, 2005)
So you, your organization, have decided to go for services marketing. The field is lucrative, the entry is easy, the potential almost unlimited, the profitability very high. And if you really are willing to service your customers, your clients, the competition is almost nonexistent. But, please wait. Services marketing is not every one’s cup of tea. "Yeh vo nagma hai jo har saaz pe gaya nehin jata" (this is a song that cannot be played on each and every musical instrument).So before you take the plunge ,before you commit yourself, please ask yourself the following four questions and answer them honestly.